Therapeutic potential of the haruan (Channa striatus) : from food to medicinal uses - Mohd Shafri, Mohd. Affendi; Mat Jais, Abdul Manan (Nutrition Society of Malaysia, 2012)
The haruan (Channa striatus) is an indigenous, predatory freshwater fish of Malaysia. It is a common food fish among the local populace with traditionally identified pharmacological benefits in treating wound and pain and in boosting energy of the sick. Channa striatus is also a subject of renewed interest in Malaysian folk medicine in the search for a better cure for diseases and ailments. Amino acids and fatty acids, found in high concentrations in the fish, might have contributed to its pharmacological properties. Important amino acids of the fish include glycine, lysine and arginine, while its fatty acids are arachidonic acid, palmitic acid and docosahexaenoic acid. They appear to effect their influence through the formation of several types of bioactive molecules. Extracts of the fish are produced from whole fish, roe, mucus and skin of the fish. This review updates research findings on potential uses of Channa striatus, beyond the traditional prescription as a wound healer, pain reliever and energy booster to include its properties as a ACE-inhibitor, anti-depressant and neuroregenerative agent. The fish appears to have wide-ranging medical uses and should be studied more intensively to unearth its other properties and mechanisms of action.